An evaluation of the comprehensibility of graphical exit signs for passenger aircraft - Morley, F. J. Joel (Cranfield University, 1997)
The purpose of this report is to present the results of a two phased study which aimed to evaluate the comprehensibility of a number of graphical exit signs for use in passenger aircraft. It is thought that the use of graphical symbols to depict this information has the advantages of being universally comprehensible without dependence on language, while requiring less space to display the signs than using multiple languages. The results of phase 1 and phase 2 are presented. Phase 1 involved the evaluation of seven graphical signs indicating three meanings: the actual location of an exit, exits located to the left and right, and that the emergency exit(s) was/were located further down the aircraft aisle (straight ahead). The second phase involved the evaluation of three graphical signs (with the same three meanings) in addition to an evaluation of the comprehensibility of their language based equivalents. An analysis of the comprehensibility of the graphical signs revealed the variants evaluated which indicated the location of the exit were sufficiently understood by members of the traveling public to be put into use. Comprehension of the current language based sign was significantly higher than the best graphical sign for this meaning. The graphical signs evaluated which indicated that the exits are located to the left and right were also sufficiently understood by the traveling public. Comprehension of the current language based sign was significantly lower than that of the best graphical sign for this meaning. The graphical signs evaluated which indicated that the exits are located further down the aisle using upwards facing arrows failed to meet the comprehension criteria. The current language based sign also failed to meet the criteria. However comprehension of the best graphical sign was found to be significantly higher than the current language based sign and as such is an improvement to what is currently used. Specific conclusions related to these signs, and general conclusions regarding the use of graphical symbols to convey this type of information are presents.